Respuesta :

#1

  • (-3,1)
  • (3,-3)

[tex]\\ \sf\longmapsto m=\dfrac{-3-1}{3+3}=\dfrac{-4}{6}=\dfrac{-2}{3}[/tex]

Slope of the line perpendicular to it (Reciprocal of line slope)

[tex]\\ \sf\longmapsto \dfrac{-3}{2}[/tex]

Option B

#2

Attached(1)

#3

Attached (2)

#4

Attached (3)

#5

  • (-3,7)
  • (3,3)

[tex]\\ \sf\longmapsto Slope=m=\dfrac{3-7}{3+3}=\dfrac{-4}{6}=\dfrac{-2}{3}[/tex]

Put in slope intercept form

[tex]\\ \sf\longmapsto y=mx+b[/tex]

[tex]\\ \sf\longmapsto 3=\dfrac{-2}{3}(3)+b[/tex]

[tex]\\ \sf\longmapsto 3=b-2[/tex]

[tex]\\ \sf\longmapsto b=3+2=5[/tex]

Equation of the line:-

[tex]\\ \sf\longmapsto y=\dfrac{-2}{3}x+5[/tex]

Option C

Ver imagen Аноним
Ver imagen Аноним
Ver imagen Аноним